The impact of vortex generator positioning and heated surface orientation on thermal performance and flow dynamics in asymmetrically heated duct - Hüseyin Zahit Demirağ (Case Studies in Thermal Engineering)
This computational investigation primarily explores the impact of three factors on thermo-hydraulic performance: the dimensionless distance ratio (z/L = −0.1 to 0.5), Heated Surface [HS] orientation (HS-Up, HS-Down), and Delta Winglet [DW] positioning (DW-PU, DW-PD). The numerical model applies steady-state RANS and energy equations with the (SST) k-ω turbulence model, assuming incompressibility, constant thermophysical properties, and ignoring radiation and buoyancy effects. A comprehensive analysis of resulting data reveals that the DW-PD configuration yields lower Darcy friction factors across all z/L ratios compared to DW-PU layout, exhibiting reductions of 6.35 % at z/L = −0.1 and 3.49 % at z/L = 0.5. The DW-PD setup with HS-Down demonstrates the best thermal performance among all configurations and dimensionless distance ratios (except z/L = −0.1). Moreover, the optimum dimensionless distance ratios for achieving the highest Nusselt numbers are determined as z/L = 0.1 for HS-Up and z/L = 0.2 for HS-Down under both configurations. The computational data indicates that the difference between the maximum and minimum Thermal Enhancement Factor [TEF] is approximately 23.78 % and the highest TEF = 1.25, is achieved with the utilization of DW-PD at z/L = 0.2 for HS-Down at Re = 5000. This study underscores the critical significance of examining all these parameters to attain the highest thermal performance.